Internet of Things (IoT) Based Water Irrigation System - Hamdi, Mohammed; Rehman, Asif; Alghamdi, Abdullah; Nizamani, Muhammad Ali; Missen, Malik Muhammad Saad; Memon, Muhamamd Ali (International Journal of Online and Biomedical Engineering (iJOE), 2021)
Agriculture plays a vital role in the economy of Pakistan. Issues concerning irrigation have been always encumbering the development of the country. Water scarcity is becoming a big issue because of climate change, insufficient services and rising population. Farmers are not receiving the supply of equitable water efficiently due to current methods of irrigation, such as inequitable water distribution, manual reporting of mogha discharge by OFWM, change of water turn at late night and no need of water at his allocated time, tail-end user problems like either too much of water supply or no availability of water as per need of farmers. One solution to this problem is a smart irrigation system in which the system uses internet of things (IoT) based sensors to monitor water levels and communicates the water situation to the user. In this research, we elaborate on the applicability of the Internet of Things (IOT) in the irrigation system and propose an architecture of IoT based water irrigation system using a wireless sensor network to solve the problems of farmers. The IoT based smart irrigation system is based on the raspberry pi to improve the productivity of water and keep costs down. Farmer is informed about fields while there is any deviance from the expected water situation by a text message.